QTc interval-dependent body posture in pediatrics - Björn Reynisson; Gustaf Tanghöj; Estelle Naumburg (BMC, 2020)
Abstract Background Syncope is a common and often benign disorder presenting at the pediatric emergency department. Long-QT syndrome may be presented with syncope, ventricular arrhythmias or sudden death and is vital to exclude as an underlying cause in children presented with syncope. Few studies have assessed QTc in relation to body posture in children. In this study, we assessed the QTc interval while laying down and during active standing in children with known long-QT syndrome compared to healthy controls. Methods Children aged 1-18 years with long-QT syndrome (N = 17) matched to two healthy controls (N = 34) were included in this case-control study. The ECG standing was performed immediately after the ECG in the supine position. The QTc interval and QTc-difference by changing the body position were calculated. Results All children with long-QT syndrome were treated with propranolol. QTc was prolonged among long-QT syndrome children while lying down and when standing up, compared to controls. A prolongation of QTc appeared when standing up for both cases and controls. There was no significant difference in QTc increase between the groups. A QTc over 440 ms was observed among four cases lying down and in eight cases while standing, but not in any of the controls. The standing test with a cut-off of 440 ms showed a sensitivity of 47% and a specificity of 100% for case-status in our study. Conclusion QTc measured on ECG when rapidly rising up is prolonged in both healthy and LQTS children. More importantly, it prolongs more in children with LQTS and increases in pathological levels.